Long-term outcomes of patients with active melanoma brain metastases treated with combination nivolumab plus ipilimumab (CheckMate 204): final results of an open-label, multicentre, phase 2 study. Issue 12 (December 2021) - Tawbi, Hussein A; Forsyth, Peter A; Hodi, F Stephen; Algazi, Alain P; Hamid, Omid; Lao, Christopher D; Moschos, Stergios J; Atkins, Michael B; Lewis, Karl; Postow, Michael A; Thomas, Reena P; Glaspy, John; et al.
Summary: Background: Combination nivolumab plus ipilimumab was efficacious in patients with asymptomatic melanoma brain metastases (MBM) in CheckMate 204, but showed low efficacy in patients with symptomatic MBM. Here, we provide final 3-year follow-up data from the trial. Methods: This open-label, multicentre, phase 2 study (CheckMate 204) included adults (aged ≥18 years) with measurable MBM (0·5–3·0 cm in diameter). Asymptomatic patients (cohort A) had an Eastern Cooperative Oncology Group (ECOG) performance status of 0 or 1 and no neurological symptoms or baseline corticosteroid use; symptomatic patients (cohort B) had an ECOG performance status of 0–2 with stable neurological symptoms and could be receiving low-dose dexamethasone. Nivolumab 1 mg/kg plus ipilimumab 3 mg/kg was given intravenously every 3 weeks for four doses, followed by nivolumab 3 mg/kg every 2 weeks for up to 2 years, until disease progression or unacceptable toxicity. The primary endpoint was intracranial clinical benefit rate (complete responses, partial responses, or stable disease lasting ≥6 months) assessed in all treated patients. Intracranial progression-free survival and overall survival were key secondary endpoints. This study is registered with ClinicalTrials.gov, NCT02320058 . Findings: Between Feb 19, 2015, and Nov 1, 2017, 119 (72%) of 165 screened patients were enrolled and treated: 101 patients were asymptomatic (cohort A; median follow-up 34·3 months [IQR 14·7–36·4]) and 18 were symptomatic (cohort B; median follow-up 7·5 months [1·2–35·2]). Investigator-assessed intracranial clinical benefit was observed in 58 (57·4% [95% CI 47·2–67·2]) of 101 patients in cohort A and three (16·7% [3·6–41·4]) of 18 patients in cohort B; investigator-assessed objective response was observed in 54 (53·5% [43·3–63·5]) patients in cohort A and three (16·7% [3·6–41·4]) patients in cohort B. 33 (33%) patients in cohort A and three (17%) patients in cohort B had an investigator-assessed intracranial complete response. For patients in cohort A, 36-month intracranial progression-free survival was 54·1% (95% CI 42·7–64·1) and overall survival was 71·9% (61·8–79·8). For patients in cohort B, 36-month intracranial progression-free survival was 18·9% (95% CI 4·6–40·5) and overall survival was 36·6% (14·0–59·8). The most common grade 3–4 treatment-related adverse events (TRAEs) were increased alanine aminotransferase and aspartate aminotransferase (15 [15%] of 101 patients each) in cohort A; no grade 3 TRAEs occurred in more than one patient each in cohort B, and no grade 4 events occurred. The most common serious TRAEs were colitis, diarrhoea, hypophysitis, and increased alanine aminotransferase (five [5%] of each among the 101 patients in cohort A); no serious TRAE occurred in more than one patient each in cohort B. There was one treatment-related death (myocarditis in cohort A). Interpretation: The durable 3-year response, overall survival, and progression-free survival rates for asymptomatic patients support first-line use of nivolumab plus ipilimumab. Symptomatic disease in patients with MBM remains difficult to treat, but some patients achieve a long-term response with the combination. Funding: Bristol Myers Squibb.